Cell Death Signaling and Anticancer Therapy - Galluzzi, Lorenzo; Vitale, Ilio; Vacchelli, Erika; Kroemer, Guido (Frontiers in Oncology, 2011)
For a long time, it was commonly believed that efficient anticancer regimens would either trigger the apoptotic demise of tumor cells or induce a permanent arrest in the G1 phase of the cell cycle, i.e., senescence. The recent discovery that necrosis can occur in a regulated fashion and the increasingly more precise characterization of the underlying molecular mechanisms have raised great interest, as non-apoptotic pathways might be instrumental to circumvent the resistance of cancer cells to conventional, pro-apoptotic therapeutic regimens. Moreover, it has been shown that some anticancer regimens engage lethal signaling cascades that can ignite multiple oncosuppressive mechanisms, including apoptosis, necrosis and senescence. Among these signaling pathways is mitotic catastrophe, whose role as a bona fide cell death mechanism has recently been reconsidered. Thus, anticancer regimens get ever more sophisticated, and often distinct strategies are combined to maximize efficacy and minimize side effects. In this review, we will discuss the importance of apoptosis, necrosis and mitotic catastrophe in the response of tumor cells to the most common clinically employed and experimental anticancer agents.